PENURUNAN KADAR MINYAK DAN COD AIR LIMBAH OPERASIONAL PEMBANGKIT LISTRIK DENGAN FLOTASI DAN LUMPUR AKTIF - Suyasa, I Wayan Budiarsa (Bumi Lestari; Vol 13 No 1 (2013), 2013)
Abstract Research about treatment of waste water power plant operation of PT Indonesia Power at Denpasar with the flotation and activated sludge method has been carried out. The objective of research is determine optimum treatment time in flotation and activated sludge to decrease oil and COD content of wastewater. In the flotation stage, 8 liters of waste water power plant operation of PT Indonesia Power aerated by aerators for 60 minutes. After the flotation treatment waste water treated by activated sludge method for 24 hours. The results of research showed that the time of treatment in the 60th minute the flotation process capable to reduce the oil contents reach 450 mg/L with the treatment effectiveness of 97,92%. At the time of treatment in the 24 hours, the activated sludge process has been able to reduce the oil content reach 0 mg/L with treatment effectiveness is 100% and reduce COD value reach 27,63 mg/L with the treatment effectiveness of 70,59%. Oil content and COD value obtained from are effluent of flotation and activated sludge below Class III Water Quality according to PerGub Bali Number 8 in 2007 (1 mg/L and 50 mg/L respectively).
Keywords: Keywords : Flotation, Activated Sludge, Oil and COD content